INTERNAL WHISTLEBLOWING INTENTIONS AMONG INDONESIAN CIVIL SERVANTS - Mahmudi Mahmudi; Nisrina Nur Aini; Herlina Rahmawati Dewi (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
Corruption is still a severe problem for many developing countries. One of the efforts to eradicate corruption is implementing a whistleblowing system. This research aims at examining the effects of professional commitment, leadership style, organizational culture, rewards, and level of retaliation towards internal whistleblowing intentions. The sample used in this research consisted of 125 Indonesian civil servants who worked in Klaten Regency, Central Java. This research indicated that professional commitment, organizational culture, leadership style, and reward had a positive and significant effect on internal whistleblowing intentions. However, the research could not show that retaliation influences internal whistleblowing intentions. This research implied strengthening professional commitment, organizational culture, leadership, and rewards that could increase whistleblowing intentions.